Effect of sera from elite athletes on cytokine secretion and insulin signaling in preadipocytes and skeletal muscle cells - Alheidous, Sara; Al-Muraikhy, Shamma; Rizk, Nasser; Sellami, Maha; Donati, Francesco; Botre, Francesco; Al-Mansoori, Layla; Elrayess, Mohamed A. (Frontiers in Molecular Biosciences, 2022)
Introduction: The immunomodulatory effect of physical activity can impact insulin signaling differentially in adipose tissues and skeletal muscle cells depending on sport intensity. In this study, the effect of serum from elite athletes who belong to different endurance and power sports on cytokine secretion and insulin signaling in preadipocyte and skeletal muscle cell lines was investigated. Methods: Preadipocytes (3T3L1) and skeletal muscle cells (C2C12) were cultured in media containing pooled sera from elite athletes who belong to high endurance (HE), high power (HP), or low endurance/low power (LE/LP) sports for 72 hours. Secreted cytokines (IL-6 and TNF-alpha) were assessed in supernatant and insulin signaling phosphoproteins levels were measured in lysates following treatment using cells multiplex immunoassays. Results: Sera from LE/LP and HP induced TNF-α secretion in C2C12, while serum from HE reduced IL-6 secretion compared to non-athlete serum control. All elite athlete sera groups caused decreased insulin sensitivity in 3T3L1 cells, whereas in C2C12 cells, only HE athlete serum reduced insulin signaling, while LE/LP and HP caused increased insulin sensitivity. Conclusion: Sera from elite athlete who belong to different sport disciplines can affect the inflammatory status and insulin signaling of preadipocytes and myoblasts differently with implications on risk of developing insulin resistance. Further investigation of the functional relevance of these effects on exercise physiology and pathophysiology is warranted.